2018
DOI: 10.1371/journal.pone.0203772
|View full text |Cite
|
Sign up to set email alerts
|

Participation experiences of people with deafblindness or dual sensory loss: A scoping review of global deafblind literature

Abstract: BackgroundDeafblindness, also known as dual sensory loss, is a varying combination of visual and hearing impairment in the same individual. Interest in this topic has increased recently due to evidence suggesting an increase in prevalence of this condition among older adults. Persons with deafblindness frequently experience participation barriers and social isolation. Developing an understanding of their experiences can inform the design of programs and policies to enhance participation of people with deafblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 68 publications
(167 reference statements)
2
87
0
2
Order By: Relevance
“… Every 6–12 months or as per clinical need [ 75 ] Speech and language therapist Assess of the sensorial impairment including speech perception, speech recognition and sound localisation and distance evaluation First referral during childhood Consider implication of sensorial impairment in the communication, social interactions, emotional wellbeing, mobility, assistive technology, habitation and rehabilitation potential. Yearly or as required [ 76 ] Social worker Support of patients and families living with disabilities, who require enhanced resources in the community First referral: from childhood to adulthood As required Expert opinion Patients’ Association Support to patients and their families Facilitate clinic and research First referral at the time of diagnosis As required [ 77 ] …”
Section: Managementmentioning
confidence: 99%
“… Every 6–12 months or as per clinical need [ 75 ] Speech and language therapist Assess of the sensorial impairment including speech perception, speech recognition and sound localisation and distance evaluation First referral during childhood Consider implication of sensorial impairment in the communication, social interactions, emotional wellbeing, mobility, assistive technology, habitation and rehabilitation potential. Yearly or as required [ 76 ] Social worker Support of patients and families living with disabilities, who require enhanced resources in the community First referral: from childhood to adulthood As required Expert opinion Patients’ Association Support to patients and their families Facilitate clinic and research First referral at the time of diagnosis As required [ 77 ] …”
Section: Managementmentioning
confidence: 99%
“…They have also been found to be interested in being involved and contributing to society (Hersh, 2013a). A scoping review revealed that participation among people with deafblindness is due to the interaction of personal and environmental factors, but called for studies focusing on lived experiences in order to increase understanding and improve services to enhance participation (Jaiswal, Aldersey, Wittich, Mirza, & Finlayson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More research is needed to inform services/policies speci c to meet the needs of the growing population of older adults with DSI. This priority is also re ected in the work of DSI researchers and the recent report by the World Federation of the Deafblind (2018) highlighting the challenges faced by people with DSI, and pinpointed to the risk of exclusion from the implementation of the United Nations Conventions on the Rights of Persons with Disabilities (UNCRPD) and the United Nations Sustainable Development Goals (2,4,32,(34)(35)(36)42). Understanding the current state of the continuum of care for older adults with DSI is paramount to nding ways to promote healthy ageing.…”
Section: Introductionmentioning
confidence: 99%